Credit default swaps as indicators of bank financial distress. (June 2019) - Avino, Davide E.; Conlon, Thomas; Cotter, John
Highlights: CDS spread changes are shown to be effective leading indicators of bank distress. CDS contain bank condition information supplemental to equity and accounting data. Findings in keeping with indirect market discipline. Results robust to a variety of alternative specifications. Abstract: We examine whether CDS contracts written on individual banks are effective leading indicators of bank financial distress during a period of systemic bank crisis. Changes in CDS spreads are found to yield a robust signal of failure across a set of European and US banks, in keeping with indirect market discipline. Furthermore, changes in CDS spreads provide information about the condition of banks which supplements that available from equity markets and contained in accounting metrics. Our findings hold out-of-sample, for various cohorts, for subordinated CDS spreads, for idiosyncratic changes in CDS and are robust to the use of alternative measures of bank distress, including rating downgrades and accounting risk.